2001
DOI: 10.1111/j.1469-8749.2001.tb00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Strength, power, and coactivation in children with developmental coordination disorder

Abstract: Strength, power, and coactivation levels were measured during knee extension and flexion tasks in 20 children (13 males, 7 females) with developmental coordination disorder (DCD) and 20 age‐matched control children (12 males, 8 females). Participants were classified according to results obtained on the McCarron Assessment of Neuromuscular Development, with each group including two age levels: 6 to 7 and 9 to 10 years. Tasks were performed on a Biodex dynamometer under isometric and isokinetic conditions with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
3
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 45 publications
2
36
3
4
Order By: Relevance
“…This would sit well with the idea that a reduced postural stability may influence the variability of walking as suggested in the ageing literature. This deficit in postural control and different walking patterns may be explained by some of the neuromuscular deficits seen in children with DCD, such as problems of muscle strength and power, and increased co-activation of muscle groups during knee flexion tasks (Raynor, 2001). Other work examining limb control has reported that children with DCD are more variable than TD peers in the timing and force of muscle contractions, both in rhythmic and discrete tasks (Lundy-Ekman, Ivry, Keele, & Woollacott, 1991;Piek & Skinner, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This would sit well with the idea that a reduced postural stability may influence the variability of walking as suggested in the ageing literature. This deficit in postural control and different walking patterns may be explained by some of the neuromuscular deficits seen in children with DCD, such as problems of muscle strength and power, and increased co-activation of muscle groups during knee flexion tasks (Raynor, 2001). Other work examining limb control has reported that children with DCD are more variable than TD peers in the timing and force of muscle contractions, both in rhythmic and discrete tasks (Lundy-Ekman, Ivry, Keele, & Woollacott, 1991;Piek & Skinner, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Test-retest reliability correlations after one month for individual items ranged between .67 and .98 for 31 adults with mental disabilities (McCarron, 1997). Concurrent validity of the test with the BOT-1 was established by an Australian research team (Tan, Parker, & Larkin, 2001) and other studies have validated its appropriateness as a motor assessment tool (O'Beirne et al, 1994;Raynor, 2001). …”
Section: Motor Performancementioning
confidence: 99%
“…1) was developed in the United States in 1982 as a screening and evaluation tool for clinicians, educators, allied health professionals and researchers. In Australia, it is one of the most commonly used tests of motor performance (Caeyenberghs, Tsoupas, Wilson, & Smits-Engelsman, 2009;Chia, Guelfi, & Licari, 2010;Hands, Larkin, Parker, Straker, & Perry, 2009;O'Beirne, Larkin, & Cable, 1994;Piek, Dawson, Smith, & Gasson, 2008;Raynor, 2001;Rose, Larkin, & Berger, 1997). Compared to the other commonly used tests, the MAND has a number of advantages.…”
Section: Introductionmentioning
confidence: 99%
“…However, follow-up analyses exploring the differences between legs, found significantly greater differences in the variability across the two limbs for children with DCD. Raynor (2001) has shown that children with DCD have neuromuscular problems including lower levels of muscle strength and power and increased levels of coactivation of muscle groups during a knee flexion task. Lundy-Ekman, Ivry, Keele, and Woollacott (1991) found similar neuromuscular problems, indicating difficulties with the selective muscle control necessary for rhythmic coordination.…”
Section: Introductionmentioning
confidence: 99%